If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+10=-5(x-4)
We move all terms to the left:
-3x+10-(-5(x-4))=0
We calculate terms in parentheses: -(-5(x-4)), so:We get rid of parentheses
-5(x-4)
We multiply parentheses
-5x+20
Back to the equation:
-(-5x+20)
-3x+5x-20+10=0
We add all the numbers together, and all the variables
2x-10=0
We move all terms containing x to the left, all other terms to the right
2x=10
x=10/2
x=5
| 5(r-9)-2(1-r)=1 | | -16/y=4 | | 5x+18=8x-28 | | 30-x/2x=7 | | -3m-2=-(-6m+2) | | 0.5(x+3)=3(0.1+0.16x) | | -6(w-5)=-8w+38 | | X2-8x-33=0 | | 9(x+3)-3x=55 | | 55+26x-1=90 | | |2x-7|=|x+4| | | 3.8x-47=1.3x+8 | | -8=-4(v+19) | | 0.6x+0.9=-0.2x-2.3 | | 6(4n-2)=40-2n | | 31=4(u-6)+7u | | x-1=1.48 | | 3/7=2/5x | | 17-s/4=-10s= | | -(j-6)=-3 | | x+3.6=9.2 | | -2y-3-(-4y+5+(-y+2-(3y-1)+2-5))=-(y-4) | | 2=7(w+2)-4w | | 55+26×-1=80x | | 11=6x-1+6x | | -8=-5v+7(v-4) | | -11-2k=1-8k | | 11x-5(2x-1)=5(6-x)+3 | | 7c-(1/3)=(7/9) | | 7x+2x-9=2(4x+8) | | -11-2k=-1-8k | | -7(9n+8)=-31-4n |